Mali's white revolution: smallholder cotton from 1960 to 2003 - Tefft, James (International Food Policy Research Institute, 2004)
One of the pillars of rural development in francophone Africa, the cotton sector serves as a principal motor of economic development, generating benefits to farmers, rural communities, private traders, cotton companies, and national governments.... Government and farmers alike consider cotton a strategic industry.... The Malian cotton model exemplifies the common vertical support system for smallholder agriculture, in which a single entity supplies inputs (usually on credit) in return for guaranteed marketing of the output, from which input costs can be deducted..... In both research and marketing, Mali has benefited from collaboration with regional cotton networks that have achieved important scale economies for many small countries in the region.... Given obvious spillovers of agroclimatic zones across contiguous African countries, this model of regional collaboration in research and marketing illustrates key benefits that could be applied to many other agricultural commodities-bananas, cassava, maize, beans, and livestock, for example.